PENGARUH FRAMING DAN URUTAN BUKTI TERHADAP AUDIT JUDGMENT: KOMPARASI DAN INTERAKSI KEPUTUSAN INDIVIDU-KELOMPOK - Haryanto, Haryanto (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
This study aims to compare type of decision maker (individual-group) on the influence offraming and order effect for making an audit judgment by the auditor. A laboratoryexperiment approach with 120 auditors from The Audit Board of The Republic of Indonesia(Badan Pemeriksa Keuangan Republik Indonesia) as participants used to hypothesistesting. The results show that framing influences an audit judgment, and the interactionbetween framing and type of decision-maker affects on audit judgment. The study alsoshows that the order effect factor influences audit judgment. The interaction between theorder of evidence and the type of decision-maker also occurs, which indicates a decisionshift of individual-group in influencing an audit judgment. Consistent with several previousstudies, the group's decision is in line and greater or smaller then individual decision hasbeen made previously.